2006
DOI: 10.1007/s00265-006-0299-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and genetic influences on mating strategies along a replicated food availability gradient in guppies (Poecilia reticulata)

Abstract: Food availability is expected to influence the relative cost of different mating tactics, but little attention has been paid to this potential source of adaptive geographic variation in behavior. Associations between the frequency of different mating tactics and resource availability could arise because tactic use responds directly to food intake (phenotypic plasticity), because populations exposed to different average levels of food availability have diverged genetically in tactic use, or both. Different popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 69 publications
(107 reference statements)
0
27
1
Order By: Relevance
“…As with many environmental gradients, stream gradients are multivariate, consisting of superimposed and correlated abiotic and biotic variables, such as temperature, precipitation, food availability, vegetation and predation (Endler, 1995; Grether et al. , 1999; Kolluru et al. , 2007; Walsh & Reznick, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with many environmental gradients, stream gradients are multivariate, consisting of superimposed and correlated abiotic and biotic variables, such as temperature, precipitation, food availability, vegetation and predation (Endler, 1995; Grether et al. , 1999; Kolluru et al. , 2007; Walsh & Reznick, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Here, ENM enabled us to disentangle the complexity of environmental differences along the elevational gradient. As with many environmental gradients, stream gradients are multivariate, consisting of superimposed and correlated abiotic and biotic variables, such as temperature, precipitation, food availability, vegetation and predation (Endler, 1995;Grether et al, 1999;Kolluru et al, 2007;Walsh & Reznick, 2009). Using ENM followed by DFA allowed us to identify abiotic factors important in predicting the distribution of parentals and their hybrids, and helped us to focus on fitness-relevant variables that were the strongest drivers of the observed patterns.…”
Section: Niche Differentiation and The Abiotic Environmentmentioning
confidence: 99%
“…Therefore, a result similar to yellow guppies would have also been obtained for black guppies, of there was a prolonged experimental period. Kolluru et al (2006Kolluru et al ( , 2007 also showed that the fin regeneration in guppies is possible even in the presence of natural stressors such as predators and infectious agents, and they regrew more fin tissues when the food level was raised. Hockley et al (2014) have shown that the swimming speed of guppies is affected by the hydrodynamic drag imposed by their fins.…”
Section: Discussionmentioning
confidence: 99%
“…Archard et al (2009) found that guppy mating behavior, especially the courtship display, is correlated with both the quantity and quality of light. Males displayed more at lower light levels and at light levels simulating dawn and dusk than at higher light levels and those simulating levels at high noon (Endler 1987;Kolluru et al 2007;Archard et. al 2009).…”
Section: Light Intensity and Relationships With Predation Risk In Thementioning
confidence: 99%
“…Males also engage in aggressive interactions with other males. These interactions include both competitive interactions in which multiple males competitively court the same females, and dominance interactions in which males interact aggressively with each other without females nearby, potentially to establish relationships with respect to future mating rights to receptive females (Kolluru and Grether 2005;Kolluru et al 2007).…”
Section: Light Intensity and Relationships With Predation Risk In Thementioning
confidence: 99%